Streptococcus dysgalactiae subsp. dysgalactiae isolated from milk of the bovine udder as emerging pathogens: In vitro and in vivo infection of human cells and zebrafish as biological models. Issue 1 (25th March 2018) - Alves‐Barroco, Cinthia; Roma‐Rodrigues, Catarina; Raposo, Luís R.; Brás, Catarina; Diniz, Mário; Caço, João; Costa, Pedro M.; Santos‐Sanches, Ilda; Fernandes, Alexandra R.
Abstract: Streptococcus dysgalactiae subsp. dysgalactiae (SDSD) is a major cause of bovine mastitis and has been regarded as an animal‐restricted pathogen, although rare infections have been described in humans. Previous studies revealed the presence of virulence genes encoded by phages of the human pathogen Group A Streptococcus pyogenes (GAS) in SDSD isolated from the milk of bovine udder with mastitis. The isolates SDSD VSD5 and VSD13 could adhere and internalize human primary keratinocyte cells, suggesting a possible human infection potential of bovine isolates. In this work, the in vitro and in vivo potential of SDSD to internalize/adhere human cells of the respiratory track and zebrafish as biological models was evaluated. Our results showed that, in vitro, bovine SDSD strains could interact and internalize human respiratory cell lines and that this internalization was dependent on an active transport mechanism and that, in vivo, SDSD are able to cause invasive infections producing zebrafish morbidity and mortality. The infectious potential of these isolates showed to be isolate‐specific and appeared to be independent of the presence or absence of GAS phage‐encoded virulence genes. Although the infection ability of the bovine SDSD strains was not as strong as the human pathogenic S . pyogenes in the zebrafish model, results suggested that these SDSD isolates are able to interact with human cells and infect zebrafish, a vertebrate infectious model, emerging as pathogens with zoonotic capability. Abstract : Bovine SDSD strains can interact with human respiratory cell lines and that this internalization is dependent on an active transport mechanism. Bovine SDSD strains are able to cause invasive infections producing zebrafish morbidity and mortality.